A Biosurfactant‐Inspired Heptapeptide with Improved Specificity to Kill MRSA. (11th January 2017) - Liu, Yuan; Ding, Shuangyang; Dietrich, Richard; Märtlbauer, Erwin; Zhu, Kui
Abstract: The emergence and rapid spread of methicillin‐resistant Staphylococcus aureus (MRSA) poses a serious threat to public health. New antibiotics and strategies are urgently needed to combat S. aureus associated infections. Bacaucin, a novel cyclic lipopeptide from Bacillus subtilis CAU21, is reported. Bacaucin shows broad antibacterial activity against Gram‐positive bacteria, but is also hemolytic and cytotoxic. However, bacaucin‐1, a bacaucin‐inspired ring‐opened heptapeptide, shows specific antibacterial activity against MRSA by a membrane‐disruptive mechanism without detectable toxicity to mammalian cells or induction of bacterial resistance. Bacaucin‐1 was efficient in preventing infections in both in vitro and in vivo models and is a valuable prototype antibiotic with high potential against S. aureus infections.